Analisis swot bank syariah indonesia dalam mendukung strategi pengembangan UMKM - Falihah, Nadiyatul (Maliki Interdisciplinary Journal, 2024)
This article discusses the important role of Micro, Small and Medium Enterprises (MSMEs) in the Indonesian economy, as well as the contribution of Bank Syariah Indonesia (BSI) in supporting the development of this sector. Using SWOT analysis, the article identifies the strengths, weaknesses, opportunities and threats faced by BSI in providing support to MSMEs. It is found that MSMEs have high resilience despite the global crisis, but still face challenges in access to financing and financial literacy. The proposed strategies to improve support to MSMEs include increasing Islamic financial literacy, developing more innovative products, and improving the quality of banking services. Through these measures, it is expected that MSMEs can develop optimally and make a significant contribution to national economic growth, create jobs, and improve people’s welfare. This article emphasizes the importance of collaboration between financial institutions and MSME players to achieve these goals.